Sublamina-Specific Dynamics and Ultrastructural Heterogeneity of Layer 6 Excitatory Synaptic Boutons in the Adult Human Temporal Lobe Neocortex. (17th September 2021) - Schmuhl-Giesen, Sandra; Rollenhagen, Astrid; Walkenfort, Bernd; Yakoubi, Rachida; Sätzler, Kurt; Miller, Dorothea; von Lehe, Marec; Hasenberg, Mike; Lübke, Joachim H R
Abstract: Synapses "govern" the computational properties of any given network in the brain. However, their detailed quantitative morphology is still rather unknown, particularly in humans. Quantitative 3D-models of synaptic boutons (SBs) in layer (L)6a and L6b of the temporal lobe neocortex (TLN) were generated from biopsy samples after epilepsy surgery using fine-scale transmission electron microscopy, 3D-volume reconstructions and electron microscopic tomography. Beside the overall geometry of SBs, the size of active zones (AZs) and that of the three pools of synaptic vesicles (SVs) were quantified. SBs in L6 of the TLN were middle-sized ( 5 μm 2 ), the majority contained only a single but comparatively large AZ ( 0.20 μm 2 ). SBs had a total pool of 1100 SVs with comparatively large readily releasable (RRP, 10 SVs L6a), (RRP, 15 SVs L6b), recycling (RP, 150 SVs), and resting ( 900 SVs) pools. All pools showed a remarkably large variability suggesting a strong modulation of short-term synaptic plasticity. In conclusion, L6 SBs are highly reliable in synaptic transmission within the L6 network in the TLN and may act as "amplifiers, " "integrators" but also as "discriminators" for columnar specific, long-range extracortical and cortico-thalamic signals from the sensory periphery.